Plant Bioactive Compounds: Crucial Pharmacological Properties and Role of Elicitors in Enhancing Production - Durga Anusha Sampath
Plant secondary metabolites play a vital role in developing numerous industrial products. Nutritive products developed from natural sources have better acceptance and demand than chemically synthesized products. Biologically active secondary metabolites play an important role in synthesizing various pharmaceutical drugs, and demand for its industrial manufacture is on the rise. In vitro cell suspension cultures using elicitors are a means of increasing the production of secondary metabolites in plant cells. Plant cells subjected to stress can be regulated to produce secondary metabolites using biotic and abiotic elicitors leading to either increase in cell volume or an increase in the rate of cell division, or both. The review aims to present the primary role of bioactive compounds and the potential of regulated in vitro cell suspension cultures in elevating the yield of pharmacologically crucial plant secondary metabolites via the active participation of various elicitors.